2017
DOI: 10.1016/j.ymthe.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Lipoproteins: A Trojan Horse Guiding Squalenoylated Drugs to LDL-Accumulating Cancer Cells

Abstract: Selective delivery of anticancer drugs to rapidly growing cancer cells can be achieved by taking advantage of their high receptor-mediated uptake of low-density lipoproteins (LDLs). Indeed, we have recently discovered that nanoparticles made of the squalene derivative of the anticancer agent gemcitabine (SQGem) strongly interacted with the LDLs in the human blood. In the present study, we showed both in vitro and in vivo that such interaction led to the preferential accumulation of SQGem in cancer cells (MDA-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 59 publications
0
38
0
Order By: Relevance
“…Cells were washed with PBS, and medium was replaced with normal medium or medium supplemented with LPDS instead of FBS. Cells were then incubated for 24 hours to enhance LDLR expression, as proven by Western blot [protocol from Sobot et al (2017a); Supplementary Fig. 2)], and subsequently treated with fluorescently labeled SQAd NPs (10 mg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were washed with PBS, and medium was replaced with normal medium or medium supplemented with LPDS instead of FBS. Cells were then incubated for 24 hours to enhance LDLR expression, as proven by Western blot [protocol from Sobot et al (2017a); Supplementary Fig. 2)], and subsequently treated with fluorescently labeled SQAd NPs (10 mg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…49,50 To monitor the impact of plasma components on the SQAd nanoparticles dispersion, we have performed SANS experiments with SQAd nanoparticles in fetal bovine serum (FBS), which, in addition to BSA, contains tens of other proteins 18 and lipoproteins particles whom previous studies have shown their importance for SQAd transport and targeting. [37][38][39] For comparison, Figure 2A first shows the SANS patterns of 0.4 mg/ml SQAd nanoparticles in D 2 O (blue circles). This signal is typical of hydrogenated spherical nanoparticles dispersed in a deuterated solvent.…”
Section: Small Angle Neutron Scattering (Sans)mentioning
confidence: 99%
“…This assumption is in line with previously proposed transport of squalene-gemcitabine by albumin. 37,39 The nanoparticles are thus playing the…”
Section: Possible Scenario Of Sqad Uptake By Bsa In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…[186][187][188] Nanomedicine formulations of gemcitabine can take advantage of the EPR effect to increase gemcitabine content within tumor tissues upon intravenous injection. [189][190][191][192] Having more gemcitabine distributed into tumor tissues will provide them the chance to kill tumor cells or inhibit tumor cell growth. …”
Section: Enhancing Distribution And/or Accumulation Of Gemcitabine Inmentioning
confidence: 99%